Análise hidrossedimentológica da bacia do alto Rio Paraíba: uma contribuição à morfodinâmica fluvial em ambientes semiáridos - Xavier, Patrícia da Conceição Dornellas da Silva (2021)
Accelerated erosive processes, silting of river beds, water flows disconnected by dams, are some manifestations in the hydrosedimentological regime and in the morphodynamics of the upper Paraíba River basin. The basin, which already had environmental problems, due to intense deforestation and an increase in the number of dams, has since 2017 had a “perennialized” river within an intermittent and ephemeral drainage network. Because it is of great importance for the management of water resources in the State, the basin was contemplated with the transposition of the São Francisco River. Although the “perennialization” of the Paraíba River is not directly the object of this research, knowledge of the flow and sediment regime, prior to “perennialization”, will allow us to understand the consequences of transposition in the future. Given this situation, the present study aims to analyze the hydrosedimentological dynamics and its morphodynamic repercussions in the basin. Several spatiotemporal scales of analysis were worked on. On the basin scale, integrated analyzes were carried out to assess the vulnerability to erosion (Crepani et al., 2001) and soil loss (USLE). Morphometric parameters were applied to know the internal morphological variations in the basin. Based on historical rainfall and flow data, the regime and spatio-temporal correlations in the basin were analyzed. The sedimentological dynamics was evaluated through the granulometry of bottom sediments and the application of the statistics proposed by Folk and Ward (1957), and the survey of river terraces as representative deposits of recent quaternary sedimentation. The results of vulnerability to erosion indicate little spatial variability and moderate degree. The estimate of soil losses was low for most of the basin, however, there were sectors with high rates, mainly in the Umbuzeiro River sub-basin. The upper Paraíba River basin is of the 7th hierarchical order (Strahler, 1952). The sub-basins of the Rivers Sucuru and Umbuzeiro are 6th order and the Monteiro River is 5th order. Drainage density and river density are low and the shape of the basins is elongated. The relief is of great altimetric amplitude, and the sub-basin of the Umbuzeiro River has the greatest variation, with a difference of 707 meters. The lithostructural influence on the longitudinal profiles of rivers is evident, since the observed anomalies coincide with lithological changes or with the occurrence of shear zones. The Paraíba River fluvial regime is of short duration in the year, 2 to 4 months, with flood peaks that occur every 2.3 years. The quarter with the highest flow is February, March and April. In 8 years, the 10 area of the Caraúbas section varied by 24%, being more due to pleasant processes than degradational ones. The bottom sediments are sandy and in 65% of the samples the average granulometry is coarse and poorly selected sand. The pattern of granodrescence was not observed, explained by the influence of the busbars on sediment transmission. The soils of the river terraces are Neossol Fluvic, with high natural fertility and high levels of sodium. These characteristics indicate that they are soils adjusted to semi-arid ambient conditions. The integrated analysis of the results (erosion, rain, flow, sediments, etc.) contributed to the understanding of the hydrosedimentological and morphodynamic dynamics of the basin. The hydrosedimentological processes in the basin are controlled by the pluviometric regime, by regularized flows and disconnection in the transmission of sediments through the busbars. Morphodynamics in the basin are intense, but governed by large and sporadic extreme rain events.